INFORMATION SYSTEM OF FIRE SAFETY IN EDUCATIONAL INSTITUTION - Andrey A. PETRIKIN (Advanced Engineering Research)
The information system role in the fire safety structure of the educational institution is considered. A model of spatial fire spread according to Monte Carlo method is offered. An example of the software implementation of this model is given.